Transport infrastructure development issues affecting the socio-economic situation in Arctic - Berezin Alexey; Orlov Nikita; Subbotina Mariia (E3S Web of Conferences, 2023)
The object of the research in this article is the transport infrastructure of the regions that are part of the Arctic zone of the Russian Federation. The authors aim to study the main socioeconomic problems that exist in the region due to the underdevelopment of transport infrastructure, as well as ways to solve them. To fulfil their research objectives, the authors used a comparative analysis method, a correlation analysis method, and a legal analysis. The study identified the specifics of the construction of transport infrastructure in the far north regions. The length of the road and rail network in the Arctic has been analysed compared with the regions of Central Russia, and the factors that limit the development of transport infrastructure have been identified. The strong dependence of freight traffic volumes on population size was revealed using the example of the Murmansk Oblast, and the main problems affecting the demographic situation in the region were identified. The problem of low passenger flow in air transportation was considered. The authors suggested the following ways of solving the problems: increasing the number of contracts PPP in their classic form, reducing the number of concession agreements, creating a transport system project based on the example of the US Interstate Highway System in the Russian Arctic, drafting a unified transport budget for all territories that make up the Arctic zone, creating a single executive authority for the Arctic zone to distribute the budget evenly.